Art museums and the incorporation of virtual reality: Examining the impact of VR on spatial and social norms. (December 2020) - Parker, Eryn; Saker, Michael
Art museums implicate established spatial and social norms. The norms that shape these behaviours are not fixed, but rather subject to change as the sociality and physicality of these spaces continues to develop. In recent years, the re-emergence of virtual reality (VR) has led to this technology being incorporated into art museums in the form of VR-based exhibits. While a growing body of research now explores the various applications, uses and effects of VR, there is a notable dearth of studies examining the impact VR might be having on the spatial and social experience of art museums. This article, therefore, reports on an original research project designed to address these concerns. The project was conducted at Anise Gallery in London, United Kingdom, between June and July 2018 and focused on the multisensory, and VR-based, exhibition, Scents of Shad Thames . The research involved 19 semi-structured interviews with participants who had just experienced this exhibition. Drawing on scholarly literature that surrounds the spatial and social norms pertaining to art museums, this study advances along three lines. First, the research explores whether the inclusion of VR might alter the practice of people watching, which is endemic of this setting. Second, the research explores whether established ways of navigating the physical setting of art museums might influence how users approach the digital space of VR. Third, the research examines whether the incorporation of VR might produce a qualitatively different experience of the art museum as a shared social space.